Métodos alternativos aos químicos para o combate do Aedes Aegypti - Silva, Rômulo Miranda Domingos da (Universidade Federal de São Carlos, 2023)
The Dengue Fever is an infectious disease caused by a virus belonging to the Flaviviridae family. It is transmitted by the bite of the female Aedes aegypti mosquito. This species of mosquito is considered cosmopolitan, that is, it is present all over the world. Control methods for this vector include surveillance, source reduction, biological control, chemical control with insecticides and repellents, among others. The control through chemical insecticides are the most popular and used, but for the same reason, it caused the resistance of the mosquito population. Alternative methods have been used to circumvent the use of chemical methods, such as biological insecticides, pathological microorganisms, predators and finally, genetically modified organisms. With two control approaches (population suppression and population replacement), GMOs are extremely viable alternatives for vector control. What can be concluded through this bibliographic review is that there are several control methods for different stages of the mosquito's life.
Aedes aegypti control strategies other than chemicals
Keywords: Controle químico; Resistência a insetos; Dengue; Chemical control; Insect resistance; Dengue fever; CIENCIAS AGRARIAS::AGRONOMIA::FITOSSANIDADE